ANTIMAGIC LABELING OF GENERALIZED SAUSAGE GRAPHS - Oudone Phanalasy (IndoMS, 2014)
An antimagic labeling of a graph with q edges is a bijection from the set of edges to the set of positive integers 1,2,...,q such that all vertex weights are pairwise distinct, where the vertex weight of a vertex is the sum of the labels of all the edges incident with that vertex. A graph is antimagic if it has an antimagic labeling. In this paper we construct antimagic labeling for the family of generalized sausage graphs.DOI : http://dx.doi.org/10.22342/jims.20.2.184.95-110